2011
DOI: 10.1039/c1dt11201e
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of aryl isothiocyanates on tetraphosphine tungsten complexes and reactivity of the resulting dithiocarbonimidate ligand

Abstract: Treatment of [WH(4)(κ(4)-P4)] (3: P4 = meso-o-C(6)H(4)(PPhCH(2)CH(2)PPh(2))(2)) with aryl isothiocyanate ArNCS at 50 °C afforded the dithiocarbonimidate-isocyanide complex [W(κ(2)-S(2)CNAr)(CNAr)(κ(4)-P4)] (4) in moderate yields. The reaction also produced ArNHCH(3) and a small amount of ArNH(2). The yield of the hydrodesulfurization product ArNHCH(3) increased when the reaction was conducted under H(2) (up to 0.65 equiv. to 3 for Ar = p-MeC(6)H(4) (Tol)). Complex 4 was proposed to be formed via reductive disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The solid-state molecular structure of 8 as determined by single-crystal X-ray analysis is presented in Figure , for which the geometric bond length values (Å) associated with the κ-( S,S )-S 2 CN t Bu fragment are as follows: Mo1–S1, 2.3694(4); Mo1–S2, 2.3763(3); S1–C24, 1.7832(12); S2–C24, 1.7963(12); C24–N3, 1.2631(15) . On the basis of literature precedent, the most likely mechanism for formation of 8 involves SAT from initial coordination of t BuNCS to a Mo­(II) center to form a transient formal Mo­(IV) terminal sulfide through elimination of t BuNC, followed by trapping of this metal sulfide with another 1 equiv of t BuNCS to form the final thermodynamically stable dithiocarbonimidate product . Thus, the fact that 8 is never observed during conversion of t BuNC and S 8 to t BuNCS strongly suggests the absence of competing SAT processes involving the ITC product that might lead to CPAM Mo IV (S) intermediates during catalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid-state molecular structure of 8 as determined by single-crystal X-ray analysis is presented in Figure , for which the geometric bond length values (Å) associated with the κ-( S,S )-S 2 CN t Bu fragment are as follows: Mo1–S1, 2.3694(4); Mo1–S2, 2.3763(3); S1–C24, 1.7832(12); S2–C24, 1.7963(12); C24–N3, 1.2631(15) . On the basis of literature precedent, the most likely mechanism for formation of 8 involves SAT from initial coordination of t BuNCS to a Mo­(II) center to form a transient formal Mo­(IV) terminal sulfide through elimination of t BuNC, followed by trapping of this metal sulfide with another 1 equiv of t BuNCS to form the final thermodynamically stable dithiocarbonimidate product . Thus, the fact that 8 is never observed during conversion of t BuNC and S 8 to t BuNCS strongly suggests the absence of competing SAT processes involving the ITC product that might lead to CPAM Mo IV (S) intermediates during catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, as Scheme terminal sulfide through elimination of t BuNC, followed by trapping of this metal sulfide with another 1 equiv of t BuNCS to form the final thermodynamically stable dithiocarbonimidate product. 25 Thus, the fact that 8 is never observed during conversion of t BuNC and S 8 to t BuNCS strongly suggests the absence of competing SAT processes involving the ITC product that might lead to CPAM Mo IV (S) intermediates during catalysis. "On-Demand" ITC Production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A very similar molecu-lar geometry is noted, and the bond lengths tend to be longer (Mo-S: 2 × 2. 45 [29]. In this case, there are small differences between the W-S bond lengths (W-S: 2.54 and 2.55 Å cf.…”
Section: Comparison Between Dithiocarbimate and Dithiocarbamate Structuresmentioning
confidence: 91%
“…The t-butyl-dithiocarbimate ligand is µ 2 -bridging, as each sulfur atom is connected to both the molybdenum and manganese atoms (Mo-S: 2.46 and 2.47 Å and Mn-S: 2 × 2.33 Å). 4) [29]. The molecular structure of the complex in 3 is represented in Figu 2c.…”
Section: Cr Groupmentioning
confidence: 99%
“…It has also been reported that two or more nitrile molecules are directly combined together on certain metal centers to form metallacyclic structures, , some of which are the possible intermediates leading to the above heterocycles or other polyfunctionalized compounds. We have been investigating transformations of unsaturated organic molecules by using the low-valent Mo and W complexes bearing tetradentate phosphine ligands . Here a unique coupling reaction of four nitrile molecules that forms a metallacyclic system on these complexes is described.…”
mentioning
confidence: 99%